Impacts of biota on bioretention cell function during establishment in the Midwest - Greene, Alicia Mathews (Kansas State University, 2009)
To understand the region-specific effects of biota on function of bioretention cells, a lysimeter study was conducted at Kansas State University to determine how earthworms and native Kansas grasses impact runoff treatment and hydraulic function of a bioretention cell. This study also employed the Comprehensive Bioretention Cell (BRC) model to demonstrate how three seasons of growth could impact bioretention cell function. The model results of the first season of growth were then compared to field data. Results indicate that the interaction of plant roots and soil macrofauna over one growing season improved several aspects of bioretention cell function. The greatest increase in saturated hydraulic conductivity was in the treatment that included both plants and macrofauna. The presence of vegetation reduced ponding effects and increased water storage. Earthworm treatments had a lesser ability to store water. All treatments were effective in reducing the concentration of P in effluent. A large amount of N was released during all events from all treatments probably because of a high initial N content of the bioretention media. No treatment performed significantly better in improving water quality, indicating that macropore flow in the earthworm treatments did not induce a higher rate of pollutant transport.
Keywords: stormwater management; BMPs; Engineering, Environmental (0775)